2020
DOI: 10.20448/journal.509.2020.71.93.99
|View full text |Cite
|
Sign up to set email alerts
|

Use of Video Blogs in Alleviating Public Speaking Anxiety among ESL Learners

Abstract: Speaking ability is one of the integral language components in English language acquisition. This ability is a challenging one to master for ESL learners, as it involves several linguistic and nonlinguistic features in presenting ideas and it is frequently associated with anxiety. Public speaking anxiety is a common issue faced by students learning a second language. Feelings such as stage fright and nervousness could contribute to their anxiety in communicating using the target language. Additionally, the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
5
14
0
Order By: Relevance
“…With respect to the recent COVID-19 pandemic and a move to online learning (Madzlan, Seng, and Kesevan 2020) found that the use of video blogs brought significant positive outcomes in reducing public-speaking anxiety among English language learners. However, a questionnaire of university students found that although online education has positive aspects, the negative elements were mainly related to a lack of communication and cooperation, as well as the general restriction of social contact in the academic context (Karalis and Raikou 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the recent COVID-19 pandemic and a move to online learning (Madzlan, Seng, and Kesevan 2020) found that the use of video blogs brought significant positive outcomes in reducing public-speaking anxiety among English language learners. However, a questionnaire of university students found that although online education has positive aspects, the negative elements were mainly related to a lack of communication and cooperation, as well as the general restriction of social contact in the academic context (Karalis and Raikou 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This research was conducted with descriptive qualitative design with a multi case type. Descriptive qualitative research design was defined as a method of conducting social science research that emphasizes gathering descriptive data in natural settings, employing inductive reasoning, and emphasizing understanding the subjects' point of view (Azmi, Hua, Abdullah, & Azman, 2021;Bogdan & Biklen, 1982;Herman, Murni, Sibarani, & Saragih, 2019;Madzlan, Seng, & Kesevan, 2020;Van Thao, Herman, Ha, Thuy, & Tho, 2020). While multi case is defined as a study which is using two or more subjects, settings, or depositories of data (Bogdan & Biklen, 1982;Van Thao, Herman, Napitupulu, Hien, & Pardede, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…With the development of Web-2.0 and computer technology, social media applications have now been widely used in education field [4].Specifically the kinds of social media applications integrated with short videos that could help provide interesting mode of learning English language communication competence for EFL language learners in the current digital arena in response to the impacts of Covid-19 pandemic on English language education [39].Previous related studies have indicated the benefits of using social media applications for English language communication education purpose such as Instagram, WhatsApp, Twitter as well as China-made Wechat and Weiblog [2,4,23,26,47].…”
Section: Using Tiktok In Teaching English Language Communication Competencementioning
confidence: 99%